THE EFFECT OF GIVING GUAVA PUDDING WITH CINNAMON WATER ON URIC ACID LEVEL OF HYPERURICEMIC PATEINTS AT PUSKESMAS BASUKI RAHMAT PALEMBANG - Iman, H.P.A; Muzakar; Susyani; Listrianah; Hendawati (International Journal of Research -GRANTHAALAYAH, 2022)
Introduction: Hyperuricemia is a condition in which uric acid level exceed normal limits, caused either by lower excretion, higher synthesis, or both. Guava is high in vitamin C and Cinnamon contains cinnamaldehyde compounds which can reduce uric acid levels. The study aimed to determine the effect of giving guava pudding with cinnamon water on uric acid level of hyperuricemic patients at Puskesmas Basuki Rahmat Palembang. Materials and Methods: This study was conducted in 2 phases. The first phase used non-factorial complete design and the second phase used quasi experiment study with pre-test and post-test with two group. Population in this study were all outpatients with hyperuricemia at Puskesmas Basuki Rahmat Palembang. The study sample was selected by purposive sampling with thirty samples in the treatment group and thirty samples in the control group. Results: showed the best pudding formulation is F2. Based on result of data analyze using paired sample t-test, there was effect between the treatment done and uric acid level of hyperuricemic patients (p=0,000). The independent t-test result indicated that there was significant comparison between the average of uric acid levels in treatment and control groups (p=0,042). Conclusion: Guava pudding with cinnamon water has effect in decreasing uric acid level of hyperuricemic patient.